- Development of an Automated Water Turbidity Monitoring and CO₂ Injection System for Aquascape Environments: - - Muhammad - Rio; Werman Kasoep; Desta Yolanda (JITCE (Journal of Information Technology and Computer Engineering), 2025)
The purpose of this research is to monitor water turbidity and automatically inject CO₂ into the aquascape, enabling aquascape enthusiasts to identify potential issues related to water quality and plant health when the system is left unattended. Key concerns include water turbidity, lighting conditions, and the distribution of CO₂ in the water. Therefore, a real-time monitoring and automated CO₂ injection system is required. The results of this study show that the system is capable of monitoring water turbidity with an average error of 2.77% and regulating CO₂ distribution based on the predefined schedule. At 13:00 WIB, the lighting is activated, and the solenoid valve opens. At 21:00 WIB, the lighting is turned off, and the solenoid valve closes. If the water becomes turbid, the buzzer automatically activates, and a notification is sent to the user via Telegram.